Early childhood education and family wellbeing - a call for Scotland to reconsider policy and practice - Julia Clark (Scottish Journal of Residential Child Care)
In 2012, Scotland’s Early Years Collaborative committed to making Scotland ‘the best place in the world to grow up’. The Scottish Government has acknowledged the importance of early support for children and families to reduce inequalities, deprivation, and health consequences throughout the lifespan. Research highlights the interconnected relationship of parental wellbeing and child wellbeing, and how this relationship can be improved through whole-family support in early childhood education and care (ECEC). This study examines cases around the world where holistic family support has been included in ECEC to improve family wellbeing. The aim of the study is to analyse how centres provide this support, and its impact on families, to identify how Scotland could promote family wellbeing in its ECEC settings. A thematic analysis was conducted, and it was found that families’ wellbeing improved through ECEC provisions that were flexible, responsive, accessible, and welcoming. Parents and practitioners equally identified collaborative partnerships with each other as one of the most important aspects of an effective ECEC program. Integration of support beyond childcare and education helped increase families’ attendance, agency, and overall wellbeing. Effective ECEC programs included support for the entire community in their philosophy of care. This community-focused philosophy of ECEC programs was found to create culturally-safe environments with a strengths-based approach to care. This study identifies three main recommendations for Scotland to promote family wellbeing in ECEC: an integration of education, health, and social services to provide holistic support for families; a pedagogical leadership structure between parents and practitioners; and ensuring programs are accessible, flexible, and responsive for families, which requires secure, long-term funding.